Analysis Effect Return on Assets (ROA), Return on Equity (ROE) and Price Earning Ratio (PER) on Stock Prices of Coal Companies in the Indonesia Stock Exchange (IDX) Period 2018-2021 - Saputra, Farhan; Nofrialdi, Reski (Dinasti Publisher, 2022)
This study aims to determine the effect of return on assets (ROA), return on equity (ROE), and price earning ratio (PER) on the stock prices of coal companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. The indicators used in this study are Return of Assets (ROA), Return on Equity (ROE), and Price Earning Ratio (PER). In this study, the three variables were analyzed partially and simultaneously to see whether there was an effect on Stock Prices. The data used in this study are ROA, ROE, PER, and Stock Prices of coal companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The number of companies is sampled as many as possible, 15 coal companies. Data analysis uses classical assumption, multiple linear regression analysis, correlation coefficient, coefficient of determination, F test, and T-test. The results of the study using the F test simultaneously show that ROA, ROE, and PER affect Stock Prices by 39%, while the T-test shows that Return on Assets (ROA) does not affect Stock Prices and Return on Equity (ROE), and Price Earning Ratio (PER) has no effect on Stock Prices.